Accuracy of Linear Measurements Made on Cone Beam Computed Tomography Scans at Different Magnifications - Ghaznavi, Aisan; Ghaznavi, Dara; Valizadeh, Solmaz; Vasegh, Zahra; Al-Shuhayeb, Muna (Journal of Contemporary Medical Sciences, 2019)
Objective: This study aimed to evaluate the accuracy of linear measurements made on CBCT (New Tom VGi) scans with different image magnifications. Methods: Forty-two titanium pins were inserted into seven dry sheep mandibles. Lengths of the pins were measured using a digital caliper with 0.01 mm readability, and the mandibles were radiographed using a CBCT unit. After reconstruction of CBCT images, three experienced radiologists measured the length and diameter of titanium pins at100%, 200% and 400% magnifications. Accuracy of measurements was analyzed using descriptive statistics and one-way analysis of variance (ANOVA) P<0.05 was considered statistically significant. Inter observer reliability was calculated using the intra class correlation coefficient (ICC) test. Results: The mean differences of linear measurements from the actual lengths of pins were 0.1960 mm, 0.2143 mm and 0.2047 mm at 100%, 200% and 400% magnifications, respectively (P>0.05). The mean differences of linear measurements from the actual diameters of pins were 0.2206 mm, 0.2063 mm and 0.1984 mm at 100%, 200% and 400% magnifications, respectively (P>0.05). Inter observer reliability of pin length measurements was estimated to be0.285, 0.707 and 0.479 at 100%, 200% and 400%magnifications, respectively. Inter observer reliability of pin diameter measurements was 0 .078, 0.469 and 0.587 at 100%, 200% and 400%magnifications, respectively. Conclusion: Based on the results, image magnification does not affect the accuracy of linear measurements made on CBCT scans. Inter observer reliability of pin length measurements was good at 200% magnification, while it was below the acceptable range at other magnifications. For measurement of pin diameters, this index was below the acceptable range at all magnifications.